Tingkat Kepuasan Pasien terhadap Pelayanan Puskesmas Buka Sampai Ndalu (Posdalu) di Puskesmas Jenggot Kota Pekalongan - Swasti Artanti; Hilda Prajayanti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
Patient satisfaction is a level of patient feeling that arises as a result of the performance of health services obtained after the patient compares it with what they expected. Puskesmas as the initial level of health services in the community have the authority and responsibility for health maintenance to achieve the highest degree of public health. The field survey on patient satisfaction is an important issue to know the results because it can be used to improve the patient satisfaction with the quality of health services. Therefore, measurement of patient satisfaction needs to be done regularly and accurately. Therefore, to find out more clearly about the condition of patient satisfaction at the puskesmas the researcher will conduct a survey with a larger sample to find out in general the Level of Patient Satisfaction with the Puskesmas Overnight Services (Posdalu) at the Jenggot Public Health Center in Pekalongan City. This type of research uses a quantitative approach with descriptive design. The population in this study were patients in Jenggot, Pekalongan City. In this study the sampling technique uses non-probability sampling technique, namely incidental sampling. The instrument in this study was using a questionnaire. Research instruments that can be accepted according to standards are instruments that have passed the validity and reliability tests. In this study the results were obtained that the level of patient satisfaction in Puskesmas (Public Health Center) Jenggot can be said to be very satisfying with a percentage of 52%.